The effect of wide preparatory stance on diving save performance in female goalkeepers - Ibrahim, R.; Kingma, I.; de Boode, V. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to investigate the effect of a wider preparatory stance on diving save performance in female goalkeepers. Five national-level goalkeepers performed dives from preferred and wide (75% of leg length) preparatory stance. Repeated measures ANOVA showed no effect of preparatory stance on dive time. Statistical parametric mapping 2-way repeated measures ANOVA was performed on the centre of mass (CoM) velocity, legs contributions, and contralateral power curves. It was found that the wider stance width required more contribution from the contralateral and less from the ipsilateral push-off, but this effect did not manifest in an improved CoM velocity or contralateral power generation. Coaches are recommended to evaluate the physiological and biomechanical differences before translating research findings between gender.